Dimensional stability of maxillary denture bases flasked with the RS tension system - Rafael L. X. Consani; Saide S. Domitti; Marcelo F. Mesquita; Lourenço Correr Sobrinho (Universidade Estadual de Campinas, 2015)
This study verified the dimensional stability of maxillary denture bases flasked with the RS tension system, in relation to the Clássico acrylic resin stages, proportioned and manipulated according to manufacturer's instructions. Fifteen maxillary wax bases were made and randomly assigned into 3 groups of 5 specimens according to the stringy, doughlike and rubbery stages of the acrylic resin. The dough of the resin was pressed in traditional metallic flasks with the aid of the RS tension system and submitted to moist heat curing cycle at 74°C for 9 hours. After the curing cycle, the flasks were allowed to cool slowly inside the curing water for 5 hours before the resin bases were removed from flasks, finished and fixed on stone casts with instantaneous adhesive. The resin base-stone cast sets were transversally sectioned into 3 sections and the base-stone gap measured at 5 points in each section. The results were submitted to ANOVA and Tukey's test and showed that the stringy, doughlike and rubbery stages presented values with statistically significant difference (p<.05) on denture bases accuracy. The best results were observed in the doughlike stage pressing, following by the stringy and rubbery stages.